Platelet phosphatidylserine exposure and microparticle production as health bioindicators in marine mammals - Felipo-Benavent, Mar; Valls, Mónica; Monteiro, Maria Céu; Jávega, Beatriz; García-Párraga, Daniel; Rubio-Guerri, Consuelo; Martínez-Romero, Alicia; O’Connor, José-Enrique (Frontiers in Veterinary Science, 2024)
In human medicine, various pathologies, including decompression sickness, thrombocytopenia, and rheumatoid arthritis, have been linked to changes in cellular microparticles (MP) formation, particularly platelet microparticles (PMP). Similar disorders in marine mammals might be attributed to anthropogenic threats or illnesses, potentially impacting blood PMP levels. Thus, detecting platelet phosphatidylserine (PS) exposure and PMP formation could serve as a crucial diagnostic and monitoring approach for these conditions in marine mammals. Our group has developed a methodology to assess real-time PS exposure and PMP formation specifically tailored for marine mammals. This method, pioneered in species such as bottlenose dolphins, beluga whales, walruses, and California sea lions, represents a novel approach with significant implications for both clinical assessment and further research into platelet function in these animals. The adapted methodology for evaluating PS exposure and PMP formation in marine mammals has yielded promising results. By applying this approach, we have observed significant correlations between alterations in PMP levels and specific pathologies or environmental factors. These findings underscore the potential of platelet function assessment as a diagnostic and monitoring tool in marine mammal health. The successful adaptation and application of this methodology in marine mammals highlight its utility for understanding and managing health concerns in these animals.